2009
DOI: 10.1029/2008ja013745
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid simulation of foreshock waves and ion spectra and their linkage to cusp energetic ions

Abstract: [1] A three-dimensional global hybrid simulation is carried out to investigate energetic ions and electromagnetic waves in the quasi-parallel (Q-k) bow shock and cusp for a typical interplanetary magnetic field configuration during the cusp energetic particle events. The bow shock, magnetosheath, and dayside magnetosphere form by interaction between the solar wind and geomagnetic dipole field. Ions of solar wind characteristics injected into the system evolve along with electromagnetic waves in a self-consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…Note that in their work, the sinusoidal waves along the magnetic field lines are only weakly compressional because the analyzed trajectory starts farther away from the shock. Also, the decrease of the amplitude of the density and magnetic field strength fluctuations when moving away from the shock is consistent with the findings of Wang et al [] using 3‐D hybrid‐particle‐in‐cell simulations and of von Alfthan et al [] using hybrid Vlasov simulations. Spacecraft observations in the terrestrial foreshock have shown evidence of similar sinusoidal waves accompanied by density variations [e.g., Eastwood et al , ].…”
Section: Simulation 2: Magnetic Cloud With a Large Bx Componentsupporting
confidence: 90%
“…Note that in their work, the sinusoidal waves along the magnetic field lines are only weakly compressional because the analyzed trajectory starts farther away from the shock. Also, the decrease of the amplitude of the density and magnetic field strength fluctuations when moving away from the shock is consistent with the findings of Wang et al [] using 3‐D hybrid‐particle‐in‐cell simulations and of von Alfthan et al [] using hybrid Vlasov simulations. Spacecraft observations in the terrestrial foreshock have shown evidence of similar sinusoidal waves accompanied by density variations [e.g., Eastwood et al , ].…”
Section: Simulation 2: Magnetic Cloud With a Large Bx Componentsupporting
confidence: 90%
“…Distribution B in the latter could be compared to the disrupted distributions (Figures 8 and 9 herein), distributions C and D are more difficult to associate. In Figure 2 of Wang et al [2009] the distributions are rather perturbed, so that they can be associated with the strongly disrupted distribution (Figure 9 herein). Distribution B also resembles a diffuse distribution (Figure 4 herein) since it shows particles streaming ahead of the core population.…”
Section: 1002/2014ja020519mentioning
confidence: 96%
“…In some cases, results of numerical models can be used to quantify mean parameters of the magnetic field in the MSH like it was presented in Rakhmanova, Riazantseva, Zastenker, and Yermolaev (2017). If features of turbulent parameters in the MSH are known, a case study of rapid plasma measurements combined with the simulated magnetic field (e.g., Wang et al, 2009) would provide interesting results.…”
Section: Variability Of Spectral Shapes In the Mshmentioning
confidence: 99%